Marketing strategy implementation in higher education. A mixed approach for model development and testing - Naidoo, Vik; Wu, T. (Routledge, 2011)
This study seeks to extend our knowledge of marketing strategy implementation in the context of international student recruitment. Strategy implementation remains an area of limited focus in the marketisation of higher education literature. Employing a mixed-design methodology on universities in the UK, US, Australia, and New Zealand, a conceptual model is presented and tested on 570 mid-level international marketing managers. Four overall constructs are found to be significant strategy implementation factors: implementation related outcome variables, dimensions of commitment, strategy, and role factors. In light of these findings, several implications are advanced for university management. The study also makes important theoretical contributions: it contributes to a growing body of literature on marketing of higher education; it adds a more nuanced theoretical foundation of marketing strategy implementation by focusing on academic institutions rather than business firms; and it enriches the theory of marketing strategy implementation by taking a cross-national analytical approach.